PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI PADA LEMBAGA PERKREDITAN DESA DI KABUPATEN BADUNG - Ni Rai Artini; Ngurah Made Novianha Pynatih; Ni Made Taman Ayuk (Universitas Mahendradatta, 2023)
The Village Credit Institution is a financial institution belonging toPakraman Village which has developed, providing social, economic and culturalbenefits to its members so that its existence needs to be fostered, improved andpreserved. The purpose of this study was to determine the direct or indirect effectof organizational culture on employee performance on job satisfaction. The location of this research was carried out at Village Credit Institutions inBadungRegency, totaling 122 LPDs. Data were collected in cross-section through a questionnaire with a Likert scale. Respondents were the employee of LPD asmany as 94 respondents. The sampling technique uses Proportionate StratifiedRandom Sampling. The data analysis method used to test the hypothesis is pathanalysis. Based on the results of the analysis it is known that: 1) organizationalculture has a direct positive and significant effect on employee performance at theLPD in Badung Regency, 2) organizational culture has a direct positive andsignificant effect on job satisfaction at the LPD in Badung Regency, 3)organizational culture has an indirect effect and significantly to the performanceof employees at LPD in Badung Regency through job satisfaction and 4) jobsatisfaction has a direct positive and significant effect on employee performanceat LPD in Badung Regency.